2017
DOI: 10.1080/14767058.2016.1183631
|View full text |Cite
|
Sign up to set email alerts
|

First trimester uterine artery Doppler, sFlt-1 and PlGF to predict preeclampsia in a high-risk population

Abstract: In a high-risk population, PlGF in the first trimester is useful for predicting preeclampsia, but neither sFlt-1 nor any UAD indices improved the prediction of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In a prospective observational study of a high-risk population of women ( n = 226), sFlt-1 did not improve prediction of PE in multivariate models combining sFlt-1, PlGF and uterine artery Doppler measurements. 21 By contrast, a recent prospective nested case–control study of low-risk participants ( n = 740) demonstrated significantly higher concentrations of first trimester sFlt-1 in women who developed PE ( n = 44). 22 However, first trimester sFlt-1 was not reported as a significant predictor variable for PE in logistic regression models.…”
Section: Discussionmentioning
confidence: 86%
“…In a prospective observational study of a high-risk population of women ( n = 226), sFlt-1 did not improve prediction of PE in multivariate models combining sFlt-1, PlGF and uterine artery Doppler measurements. 21 By contrast, a recent prospective nested case–control study of low-risk participants ( n = 740) demonstrated significantly higher concentrations of first trimester sFlt-1 in women who developed PE ( n = 44). 22 However, first trimester sFlt-1 was not reported as a significant predictor variable for PE in logistic regression models.…”
Section: Discussionmentioning
confidence: 86%
“…They reported a PE detection rate of 50% with a FPR of 10% by using only maternal body mass index (BMI) and mean artery pressure at 34 weeks of pregnancy and a detection rate of 75% with the addition of UtA PI and more than 95% with the addition of PIGF and PAPP-A values (24). However, Diguisto et al (25) reported that the multivariate model adjusted according to laboratory and sonographic indicators had an area under the curve (AUC) estimated at 0.76, which was not significantly different from the AUC of the univariate model adjusted only for PlGF (p=0.7). As a result, in a high-risk population, PlGF in the first trimester is useful for predicting PE, but neither sFlt-1 nor any UtA Doppler indices improved the prediction of PE (25).…”
Section: Discussionmentioning
confidence: 93%
“…However, Diguisto et al (25) reported that the multivariate model adjusted according to laboratory and sonographic indicators had an area under the curve (AUC) estimated at 0.76, which was not significantly different from the AUC of the univariate model adjusted only for PlGF (p=0.7). As a result, in a high-risk population, PlGF in the first trimester is useful for predicting PE, but neither sFlt-1 nor any UtA Doppler indices improved the prediction of PE (25). Li et al (26) demonstrated that UtA PI at early secondtrimester was increased in pregnancies that developed PE (1.61±0.047 vs. 1.02±0.049, p<0.001).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported various proportions of occurrence of PE among high-risk pregnant women (14) . Diguisto et al (15) conducted a study aiming at evaluation of the accuracy of uterine artery Doppler in the first trimester for preeclampsia screening. In accordance to this study, they prospectively enrolled women at high risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%